The effect of the color of LED lights on some blood indicators and the level of health status for the broiler (Latakia University Journal -Biological Sciences Series, 2020)
To verify the importance of applying a modern light system of high-energy LED LEDs, which are energy-efficient, which provides comfort to the bird's retina, and to assess their effect on some blood indicators, the level of health of the broilers, and to determine the most appropriate lighting color that enhances the calm and well-being of birds, A study was conducted on 300 broiler chickens (ROSS) in one of the private poultry in Al-Haffa area of ​​Lattakia governorate. The chicks were randomly distributed at the age of one day within five different treatments according to the LED color used (green G, blue B, mix of blue and green B+G, white W, yellow Y) And by 60 chicks per transaction, and combine One treatment three replicates of 20 thieves to duplicate one, and all the conditions of shelter, care, nutrition, and one for all transactions.     The results showed a significant increase in the red blood cell count in the blood of TMIX (2,92), (2,87) TB and TG (2,77) coefficients compared to the two treatments (TW (2,61) and TY (2,56). The results also indicated a significant increase in the leukocyte count in the treatment birds TY (26,86) TW (26,96), while it was close to the three treatment birds (TG, TMIX, TB) and there were no significant differences (0,05